191 Radiological endovascular embolization of small pelvic arteries in patients with complicated uterine cervix cancer: single-center experience in belarus. (18th September 2019) - Matylevich, O; Akinfeev, V; Mirilenko, L; Sukonko, O
Abstract : Objectives: To conduct the efficacy of radiological endovascular embolization of small pelvis arteries in patients with locally advanced and recurrent uterine cervix cancer (UCC) complicated with hemorrhage. Methods: 81 patients were included: 68 (84%) primary patients with locally advanced UCC and 13 (16%) – with UCC recurrences, who underwent radiological endovascular occlusion of small pelvis arteries regarding bleeding from tumor. Results: Distribution of primary patients according to FIGO stages: IIB stage – in 4 (6%), IIIB – in 44 (65%), IV – in 20 (29%). In the result of the procedure hemorrhage was stopped in 76 (94%) patients. After successful conduction of radiological endovascular hemostasis in 68% (46 of 68) of primary UCC patients' antineoplastic treatment was performed, according to the radical program in full – in 43% (29 of 68) of cases. Survival of 22 (32%) patients who was not treated further, and 46 (68%) patients who continued the treatment was significantly differed. 1-year adjusted survival (AS) was 15.2% (SE 8.1%) and 53.5% (SE 7.4%), respectively. No patient survived to 5 years in the first subgroup, in the second subgroup a 5-year AS was 24.0% (SE 6.8%), median AS for the first subgroup was 5.4 months, for the second – 12.8 months (p <0.001). Conclusions: Arterial embolization of pelvic vessels is an effective method of arrest of hemorrhage in patients with locally advanced and recurrent UCC in 94% of cases. Conduction of this procedure in primary patients in case of complicated locally advanced UCC allows to perform special antitumor treatment in 68% of cases.